The impact of Mobile Legends Game on students' interest in learning and prayer discipline islamic religious education of Muhammadiyah University of Yogyakarta - Awahab, Apryansyah; Tumin, Tumin (ARKA INSTITUTE, 2025)
This study investigates the impact of the Mobile Legends game on learning interest and prayer discipline among Islamic Religious Education students at Universitas Muhammadiyah Yogyakarta. As a highly popular game among students, Mobile Legends not only serves as entertainment but also influences academic and spiritual aspects. Using a qualitative approach with a descriptive phenomenology method, data were collected through in-depth interviews with six active players and participatory observation, both directly and via digital platforms. Data were analyzed using thematic analysis, and validity was ensured through triangulation and member checking. The findings reveal that excessive involvement in playing negatively affects learning interest. Students often postpone studying, lose concentration, and experience reduced academic motivation, particularly when striving for higher in-game rankings. Moreover, gaming habits influence prayer discipline; many respondents admitted to delaying or missing prayers due to gameplay. Some expressed guilt and discomfort after neglecting this religious duty. This phenomenon highlights that without strong self-control and effective time management, Mobile Legends can disrupt students' academic performance and spiritual commitments. Therefore, collective awareness is essential to promote wise technology use, ensuring it supports rather than hinders their primary roles as learners and devout individuals.